2015
DOI: 10.1242/bio.201410942
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin S and C affect protein export in Plasmodium falciparum-infected erythrocytes

Abstract: Malaria is a potentially deadly disease. However, not every infected person develops severe symptoms. Some people are protected by naturally occurring mechanisms that frequently involve inheritable modifications in their hemoglobin. The best studied protective hemoglobins are the sickle cell hemoglobin (HbS) and hemoglobin C (HbC) which both result from a single amino acid substitution in β-globin: glutamic acid at position 6 is replaced by valine or lysine, respectively. How these hemoglobinopathies protect f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 65 publications
6
56
0
Order By: Relevance
“…It is known that actin is highly susceptible to oxidative stress and that oxidation impacts on actin polymerization and dynamics10303132. If host actin reorganization is impaired, then the actin network that connects the Maurer's clefts with the knobs cannot form and vesicular trafficking of adhesins to the host cell surface is compromised13. Moreover, Maurer's clefts do not properly develop because their morphology depends on a functional actin network, as previously shown for parasitized HbAA erythrocytes treated with cytochalasin D, an inhibitor of actin polymerization10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that actin is highly susceptible to oxidative stress and that oxidation impacts on actin polymerization and dynamics10303132. If host actin reorganization is impaired, then the actin network that connects the Maurer's clefts with the knobs cannot form and vesicular trafficking of adhesins to the host cell surface is compromised13. Moreover, Maurer's clefts do not properly develop because their morphology depends on a functional actin network, as previously shown for parasitized HbAA erythrocytes treated with cytochalasin D, an inhibitor of actin polymerization10.…”
Section: Discussionmentioning
confidence: 99%
“…P. falciparum FCR3 CSA were cultured with different haemoglobinopathic erythrocytes (HbAA, HbAS, HbAC and HbF) or pretreated erythrocytes for at least two cycles, and 5 × 10 6 infected erythrocytes (trophozoite stage) were applied onto these spots for 1 h. After multiple washing steps, the adherent cells were fixed with 2% glutaraldehyde for at least 2 h. After staining for 10 min with 10% Giemsa, three randomly selected areas from each spot were imaged using a Zeiss Axiovert 200M microscope (objective × 10/0.25 air differential interference contrast (DIC)). The amount of adhesive parasites were quantified using ImageJ as previously described13. Namely, the Giemsa-stained infected erythrocytes per image were automatically counted, using thresholding and watershed functions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, vesicle-like structures positive for PfEMP1 were seen both on these actin filaments and on structures termed 'tethers' that were observed to attach Maurer's clefts to the red blood cell periphery [29,84,87,88]. However, newer work also showed impaired trafficking across the PVM in parasites growing in HbC or HbS red blood cells and this might be a further reason for the reduced cytoadherence of these red blood cells [89].…”
Section: Sorting Of Exported Proteins In the Host Cellmentioning
confidence: 99%
“…In support of this latter hypothesis, two recently-published studies have shown that in static adhesion assays, VAR2CSA-expressing FCR3 parasites in HbAS and HbAC erythrocytes exhibit significant reductions in adherence to CSA compared to those grown in HbAA erythrocytes, this decreased binding being much greater for parasitized HbAC than HbAS erythrocytes 26, 27 . However, these studies assessed only a single parasite strain in static but not flow adhesion assays.…”
Section: Discussionmentioning
confidence: 76%